2015
DOI: 10.1111/ped.12694
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Meckel diverticulum: Obstruction due to a short mesodiverticular band

Abstract: This is the first report of symptomatic Meckel diverticulum in a newborn, in which direct compression by a short mesodiverticular band (MDB) caused intestinal obstruction. A short MDB can cause intestinal obstruction due to direct compression. There are two mechanisms by which Meckel diverticulum with MDB can cause intestinal obstruction: internal hernia and direct compression. Onset of intestinal obstruction due to direct compression by a short MDB might be earlier than that for internal hernia with long MDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Many cases of volvulus and intestinal obstruction have been reported (KIM, CHA, LEE et al, 2008;ALTAF and AREF, 2014;BĂLĂLĂU, BACALBAŞA, MOTOFEI et al, 2015). Chances of intestinal obstructions increase when there are peritoneal bands or fibrous bands attaching the diverticulum to various other structures (MCANENY, RAPO and GRINDLINGER, 1989;KUNITSU, KOSHIDA, TANAKA et al, 2015). Intussusception is another complication as reported by many studies (ANWAR, AHMED, AL HINDI et al, 2014;LUBSZCZYK, KALISZEWSKI and STRUTYŃSKA-KARPIŃSKA, 2015;HUNTINGFORD, MONTALTO and CHOUDHRY, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Many cases of volvulus and intestinal obstruction have been reported (KIM, CHA, LEE et al, 2008;ALTAF and AREF, 2014;BĂLĂLĂU, BACALBAŞA, MOTOFEI et al, 2015). Chances of intestinal obstructions increase when there are peritoneal bands or fibrous bands attaching the diverticulum to various other structures (MCANENY, RAPO and GRINDLINGER, 1989;KUNITSU, KOSHIDA, TANAKA et al, 2015). Intussusception is another complication as reported by many studies (ANWAR, AHMED, AL HINDI et al, 2014;LUBSZCZYK, KALISZEWSKI and STRUTYŃSKA-KARPIŃSKA, 2015;HUNTINGFORD, MONTALTO and CHOUDHRY, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…In addition to our 2 cases, the review of the literature showed 8 other cases of symptomatic MDB in pediatric patients (Table 1 ). [ 5 , 12 – 17 ] The age of onset ranged from 10 days to 12 years. All cases reported an intestinal occlusion as the clinical picture at onset.…”
Section: Discussionmentioning
confidence: 99%
“…Kunitsu et al reported that a relatively long MDB can lead to pathogenesis over a wide age range, from childhood to adulthood, with regard to the internal hernia of an intestinal loop. [ 17 ] In contrast, a short MDB can exert direct compression on the digestive tract before or shortly after birth.…”
Section: Discussionmentioning
confidence: 99%
“…6 Rarely, direct compression of the small bowel by the mesodiverticular band, rather than an internal hernia, as in our case, may be the cause of small bowel obstruction due to mesodiverticular band, as has been described in a newborn. 2 Other rare complications associated with a mesodiverticular band have included axial torsion of the diverticulum itself due to the band 7 and aneurysmal rupture of a mesodiverticular band artery, with significant peritoneal hemorrhage, 8 both in adults.…”
Section: Discussionmentioning
confidence: 99%